Dikotomi Sunnī-Syī‘ī: Teologis atau ‘Asabiyyah - Zainal Abidin (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2012)
Sunnite (Sunnī) and Shi‘ite (Shī‘ī) are two Islamic schools which emerged after the death of the Prophet. Basically, the Sunnī-Shī‘ī dichotomy cannot be separated from pre-Islamic Arab history, which culturally adored tribal loyalty (asabiyya.) At the beginning of its appearance, in socio-cultural historical perspective, the dichotomy emerged because of the tribal-political interest, particularly, after the battle of Siffīn. This Sunnī-Shī‘ī dichotomy in the early days was actually the rivalry between the Umayyad clan and Banū Hashimite (Hāsyimiyya) clan, and served as the legacy of pre-Islamic Arab history. In the next period, to justify its existence, each of these groups looked for nass (Qur’ānic text) to strengthen its view. Consequently, the problem formerly served as the only tribal-political issues developed into a theological issue, and hence inherited conflict beyond the context of its period. The conflict that had become the part of long history of the two schools automatically established a certain paradigm and reason to their adherents, in which such paradigm also brought about different concept of epistemology. Therefore, it is difficult to reconcile the two schools, even though is not impossible at all to do conversely; let alone when a dialogue established to reconcile the two school employs phenomenological or brotherhood (ukhuwwa) approaches, and avoids apologetic approach.